Synthesis and characterization of high refractive index polyimides derived from 2, 5‐Bis(4‐Aminophenylenesulfanyl)‐3, 4‐Ethylenedithiothiophene and aromatic dianhydrides. Issue 7 (19th February 2015) - Yeo, Hyeonuk; Lee, Jiye; Goh, Munju; Ku, Bon‐Cheol; Sohn, Honglae; Ueda, Mitsuru; You, Nam‐Ho
ABSTRACT The authors describe the synthesis and characterization of the polyimide (PI) series containing a 2, 5‐bis(4‐aminophenylenesulfanyl)‐3, 4‐ethylenedithiothiophene (APSEDTT) moiety in their main chain. The APSEDTT monomer with high sulfur content was prepared and polymerized with several aromatic dianhydrides such as 4, 4′‐[p‐thio bis(phenylenesulfanyl)]diphthalic anhydride (3SDEA), 4, 4′‐biphthalic anhydride (BPDA), and 4, 4′‐oxydiphthalic anhydride (ODPA) by the traditional two‐step polycondensation procedure. All PIs exhibited high transparency, higher than 75% at 550 nm for a thickness of about 20 μm and good thermal properties such as thermal decomposition temperatures (T10%) in the range of 409–521 °C. In addition, the PIs have extraordinarily excellent optical properties in refractive index and birefringence as originally designed. In particular, the PI derived from APSEDTT and 3SDEA showed a high refractive index (1.7586), and a low birefringence (0.0087) because of their very high sulfur content (27.7%). © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 944–950